Studies in law, politics, and society. Volume 63 - Sarat, Austin (Bingley, U.K. : Emerald, 2014)
The articles in this 63rd volume of Studies in law, politics and society cover cutting edge issues of major interest to policy makers, activists and interdisciplinary law scholars : family law, the way law deals with children, international human rights, and the way law deals with injury and damages claims.
Where injury or damage is feared : peace bonds as counter-law? / Brandon Chase -- "Families in all their subversive variety" : over-representation, the ethnic child protection penalty, and responding to diversity whilst protecting children / Lucinda Ferguson -- The gracious spaces of children's law : innocence and culpability in the construction of a children's court / Akhila L. Ananth -- The dialectics of wrongful life and wrongful birth claims in Israel : a disability critique / Sagit Mor -- Human rights in context : international law and spatial injustice in New Orleans, Louisiana / Jean Carmalt -- Mitigation versus individualism : examining judges' capital sentencing decisions / Ross Kleinstuber.
Includes index.
Print version record
Keywords: Law -- General; Law -- Family Law -- Children; Law & society; Family law: children; Human rights & civil liberties law; Sociological jurisprudence; Political sociology